2017
DOI: 10.1111/fog.12218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions on the seasonal and inter‐annual variability of small pelagic fish abundance off North‐West Africa: The case of both Senegalese sardinella

Abstract: The objective of this study was to assess the effect of environmental variations on the abundance of Sardinella aurita and Sardinella maderensis in Senegalese waters in the upwelling system. Monthly data indicating the abundance of sardinella were first estimated from commercial statistics, using Generalized Linear Model from 1966 to 2011. Abundance indices (AIs) were then compared with environmental indices, at the local scale, a Coastal Upwelling Index (CUI) and a coastal Sea Surface Temperature (SST) index,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 53 publications
4
68
2
2
Order By: Relevance
“…These results seem to suggest that at this stage, sardinella prefer oceanographic conditions in the summer. These results are in accordance with previous studies which suggest that variability in abundance and distribution of sardinella is mainly under the influence of oceanographic changes, such as cooling or warming waters (Bacha et al., ; Sabatés et al., ; Thiaw et al., ; Zeeberg et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results seem to suggest that at this stage, sardinella prefer oceanographic conditions in the summer. These results are in accordance with previous studies which suggest that variability in abundance and distribution of sardinella is mainly under the influence of oceanographic changes, such as cooling or warming waters (Bacha et al., ; Sabatés et al., ; Thiaw et al., ; Zeeberg et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…This study is consistent with the findings of previous work which showed that the dynamics of small pelagic are closely linked to oceanographic conditions (Bacha et al., ; Bakun, ; Cury & Roy, ; Diankha, Thiaw, et al., ; Diankha, Wade, et al., ; Fréon, ; Fréon & Mendoza, ; Thiaw et al., ). The use of GAM, which takes into account the potentially complex non‐linear relationships between the covariates, allowed a better illustration of the links between S. aurita, as well as S. maderensis and the oceanographic conditions in off Senegal.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations